2011
DOI: 10.1103/physreve.83.026306
|View full text |Cite
|
Sign up to set email alerts
|

How water droplets evaporate on a superhydrophobic substrate

Abstract: Evaporation of water droplets on a superhydrophobic substrate, on which the contact line is pinned, is investigated. While previous studies mainly focused on droplets with contact angles smaller than 90 • , here we analyze almost the full range of possible contact angles (10 • -150 • ). The greater contact angles and pinned contact lines can be achieved by the use of superhydrophobic Carbon Nanofiber substrates. The time-evolutions of the contact angle and the droplet mass are examined. The experimental data i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
182
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(193 citation statements)
references
References 31 publications
9
182
0
2
Order By: Relevance
“…1 we plot J/(Dc s R d ) as a function of θ. Careful experiments with small partially wetting drops with pinned contact lines have confirmed the theoretical result (2.5) quantitatively over a wide range of contact angles (Gelderblom et al 2011). …”
Section: A Single Small Dropsupporting
confidence: 50%
See 3 more Smart Citations
“…1 we plot J/(Dc s R d ) as a function of θ. Careful experiments with small partially wetting drops with pinned contact lines have confirmed the theoretical result (2.5) quantitatively over a wide range of contact angles (Gelderblom et al 2011). …”
Section: A Single Small Dropsupporting
confidence: 50%
“…While in this case it is often observed that drops are either pinned completely (i.e. the radius is constant, (Gelderblom et al 2011)) or perform a stick-slip motion (Cazabat & Guéna 2010), for our systems we observe the drop radius to shrink continuously during evaporation without pinning. We attribute this to our careful sample preparation, described in detail below.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…For Knudsen diffusion to be the limiting case, the mean free path needs to be greater than the average pore diameter in the media, and for normal diffusion to become dominant, the mean free path has to be smaller than the average pore diameter [40]. The diffusion coefficient of water vapor in air, Da, is 25 x 10 -6 m 2 /s [41,42]. The mean free path of water vapor () at standard temperature and pressure (25° C, 1 bar) is calculated as 0.12 µm using the following equation [43,44]:…”
Section: Gas Diffusion and Moisture Permeabilitymentioning
confidence: 99%